2011
DOI: 10.1016/j.limno.2009.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Bank filtration in the sandy littoral zone of Lake Tegel (Berlin): Structure and dynamics of the biological active filter zone and clogging processes

Abstract: a b s t r a c tThis study focused on clogging processes and on the benthic microalgal and meiofaunal assemblage in the sandy littoral zone of Lake Tegel, which are significantly involved in bank filtration, in a long-term. Our approach combined field studies and ''in situ'' experiments to highlight the structure of the biological active filter zone as well as the mechanisms and effects of clogging in the interstices that influence the infiltration process.Campaigns to measure ''in situ'' infiltration rates and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 45 publications
5
49
0
1
Order By: Relevance
“…For example, Hoffmann and Gunkel [14] analyzed sediment cores of Lake Tegel and reported that 17-21% of the total sediment volume was filled with suspended or attached particulate organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hoffmann and Gunkel [14] analyzed sediment cores of Lake Tegel and reported that 17-21% of the total sediment volume was filled with suspended or attached particulate organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term temperature monitoring studies are mainly performed in the centre of a lake [8], water of littoral zones under calm conditions are liable to stronger heating and cooling with an up-or downwelling of water. Particularly, shallow areas are highly relevant for bank filtration, because sediments are disaggregated by waves and meiofauna activities [9]. In contrast, deeper parts of a lake are often characterized as muddy with deposited organic material, which is slowly degradable under oxygen depression.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1985, the P concentration caused by the inflow of Nordgraben and Tegeler Fließ has been reduced by an industrial-scale plant (German abbreviation: OWA) [44]. Nowadays, the nutrient status of the water bodies is mesotrophic [45], but the phosphorus content in sediment is still high (sediment samples from 2015 showed phosphorus contents between 0.647 and 1.280 kg P/Mg DM). Similarly, the additionally analyzed aquatic macrophytes Myriophyllum sp.…”
Section: Discussionmentioning
confidence: 99%